APLIKASI MOBILE LEARNING PEMBELAJARAN VIDEO EDITING BERBASIS ANDROID PADA PERSATUAN PEMUDA SANDYA KARYA MUDA DESA REKSOSARI KEC SURUH KABUPATEN SEMARANG - Setiyo Adi Nugroho; Andik Prakasa Hadi; Rudjiono Rudjiono; Ahmad Zainudin (STEKOM PRESS, 2022)
The advances in mobile technology have created a new learning method known as mobile learning technology or mobile learning. This method utilizes the use of smartphones which have become part of the daily life of people of all ages and levels of education. in this mobile learning ,android platform is selected. The reason for choosing android is that it is the most popular mobile OS. This learning is designed to run on Android with the aim that it can be used easily and can be run at any time as long as you carry an Android cellphone and there is an internet connection. This application is addressed to the Persatuan pemuda sandya karya mandiri desa reksosari kec suruh kabupaten Semarang, which is an activity of a youth group that is trying to develop and improve their video streaming channel . they need learning to improve their digital video processing skills to improve the quality of their video output. because this youth union consists of various ages and various educational backgrounds, the making of learning videos must be easy to operate, easy to display and does not require complicated equipment. The development of this application is based on usability which is the most important aspect of an application.